1999
DOI: 10.1029/1999gb900067
|View full text |Cite
|
Sign up to set email alerts
|

Stability of elemental carbon in a savanna soil

Abstract: Abstract. We have investigated the stability of oxidation-resistant elemental carbon (OREC) in a sandy savanna soil at the Matopos fire trial site, Zimbabwe. The protection of some soil plots from fire for the last 50 years at this site has enabled a comparison of OREC abundances between those plots which have been protected from fire and plots which have continued to be burnt. The total 0-5 cm OREC inventory of the soil protected from fire is estimated to be 2.0-k-_0.5 mg cm-2; approximately half the "natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
195
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(205 citation statements)
references
References 26 publications
7
195
1
2
Order By: Relevance
“…While individual charcoal particles found in soils have 14 C ages of up to several thousand years (Gavin, 2003;Sanborn et al, 2006), other studies have determined mean residence times of black C of only a few decades (Bird et al, 1999). These differences may largely be caused by different charring temperatures since Baldock and Smernick (2002) showed that the degradability of charred wood decreased with increasing heating temperature.…”
Section: Ekschmittmentioning
confidence: 99%
“…While individual charcoal particles found in soils have 14 C ages of up to several thousand years (Gavin, 2003;Sanborn et al, 2006), other studies have determined mean residence times of black C of only a few decades (Bird et al, 1999). These differences may largely be caused by different charring temperatures since Baldock and Smernick (2002) showed that the degradability of charred wood decreased with increasing heating temperature.…”
Section: Ekschmittmentioning
confidence: 99%
“…This is probably because biochar also undergoes biodegradation, although it is considered stable in the soil system. According to Bird et al (1999), the time required for biodegradation of soil-charred particles is related to their granulometry. These authors estimated that the half-life of particles smaller than 2 mm is lower than 50 years and that of particles larger than 2 mm is lower than 100 years.…”
Section: Soil Propertiesmentioning
confidence: 99%
“…Beyond feedstock type and production conditions, a wide range of additional factors, such as soil type, climate, and other environmental conditions, might strongly influence biochar carbon stability in soils (e.g., Mašek et al 2013;Schmidt et al 2011;Bird et al 1999). For this reason, great uncertainties remain concerning the precise fraction of biochar carbon that remains stable in the long-term (e.g., Mašek et al 2013;Shackley et al 2011).…”
Section: 1) Carbon Sequestration With Biocharmentioning
confidence: 99%
“…62 While Lehmann et al (2008) also arrived at MRTs of 718-9,259 years for biochar from vegetation fires in Australian soils, however, the MRT of naturally occurring biochar in Zimbabwean savannah soils ranged only from decades to centuries (Bird et al 1999) and that in Kenyan soils was even less with 8.3 years (Nguyen et al 2008). 63 These mixed results suggest that biochar stability in soil depends on a variety of factors and cannot be determined conclusively, not least due to methodological differences and shortcomings in quantifying biochar and/or its stable fraction in soils (e.g., Preston and Schmidt 2006;Hammes et al 2007).…”
Section: 1) Carbon Sequestration With Biocharmentioning
confidence: 99%